A biomass blended membrane material and its preparation method and application
By blending tannic acid with PVDF and DMAC, a biomass blend membrane material with efficient adsorption and separation capabilities was prepared, which solved the problem of difficulty in removing heavy metals and organic pollutants in heavy metal-containing wastewater in the existing technology, and achieved To achieve efficient and economical sewage treatment effect.
Patent Information
- Application Number
- CN202311484441.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-11-09
AI Technical Summary
The prior art is difficult to effectively remove heavy metal ions and organic pollutants in wastewater containing heavy metals. Traditional adsorbent materials are difficult to blend in particle form, and conventional membrane treatment cannot efficiently separate heavy metals.
Tannic acid (TA) was blended with polyvinylidene fluoride (PVDF) and N,N dimethylacetamide (DMAC) to prepare a biomass blend membrane material with a typical ultrafiltration membrane asymmetric structure. The principle of coordination between hydroxyl groups and iron ions improves the hydrophilicity and acid resistance of the membrane.
The efficient adsorption and removal of heavy metal ions is realized, the adsorption efficiency is close to 100%, and it has long -term membrane regeneration and efficient separation capabilities. The interception rate of organic pollutants can reach up to 97.84%, which is suitable for sewage treatment.
Smart Images

Figure CN117282283B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic materials, and specifically relates to a biomass blended membrane material and a preparation method and application thereof. Background Art
[0002] With the continuous development of industrial manufacturing, water pollution has become increasingly prominent. Unlike general domestic sewage, smelting and printing and dyeing wastewater usually contains rich metal ions and organic pollutants. The treatment methods are complicated, mainly ion exchange, flocculation and precipitation, etc. These methods usually require additional additives, high energy consumption and low efficiency. Membrane treatment technology has the advantages of high separation effect and low energy consumption, and has high potential for sewage treatment. Ultrafiltration membrane, as a high-efficiency separation membrane, can intercept a large amount of protein and organic pollutants. However, ultrafiltration membrane has almost no removal ability for heavy metal ions.
[0003] Wastewater containing heavy metal ions (such as iron, copper, lead, etc.) such as electroplating wastewater and printing and dyeing wastewater cannot be filtered and removed by conventional water treatment membranes and usually require deep treatment. Therefore, the development of membrane technology that can effectively separate heavy metals has become one of the important directions of current research.
[0004] As we all know, there are many adsorbable materials, but most of them can only adsorb heavy metals and cannot remove other pollutants. For example, materials such as activated carbon with heavy metal adsorbents added. To avoid this defect, it is possible to consider blending the adsorbent material into the membrane to obtain the dual effects of metal adsorption and pollutant interception. However, traditional adsorbent materials exist in the form of particles and are difficult to blend, so we consider using small organic molecules to improve the adsorption performance of the membrane. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a biomass blended membrane material.
[0008] To solve the above technical problems, the present invention provides the following technical solutions: a biomass blended membrane material, characterized in that the casting liquid formula of the biomass blended membrane material includes tannic acid TA, polyvinylidene fluoride PVDF and N,N-dimethylacetamide DMAC; wherein the weight of TA accounts for 0.5-2% of the total weight of PVDF and DMAC.
[0009] As a preferred embodiment of the biomass blended membrane material of the present invention, the biomass blended membrane material has a typical ultrafiltration membrane asymmetric structure of a skin layer, finger-shaped pores and a bottom layer of sponge pores, wherein, in a membrane thickness of 150 microns, the finger-shaped pores of the blended membrane occupy about 70% of the membrane thickness.
[0010] As a preferred embodiment of the biomass blended membrane material of the present invention, the membrane thickness of the biomass blended membrane material is 10 to 100 microns, and the water flux is 100 Lm -2 h -1 ~200L m -2 h -1 .
[0011] As a preferred embodiment of the biomass blended membrane material of the present invention, the biomass blended membrane material has hydrophilicity, acid resistance, long-term membrane regeneration ability and high-efficiency separation ability.
[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a biomass blended membrane material, characterized in that it comprises:
[0013] The TA powder, PVDF powder and DMAC organic solvent are mixed, heated and stirred to prepare a film casting solution;
[0014] The casting solution is spread evenly on a dry carrier, the film is scraped, and placed in deionized water to obtain a PVDF / TA mixed matrix membrane, which is a biomass blend membrane.
[0015] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the TA powder, PVDF powder and DMAC organic solvent is 0.1-0.4:2.8:17.2.
[0016] As a preferred embodiment of the preparation method of the present invention, the heating and stirring comprises the following steps: the heating temperature is 50 to 80° C., the stirring rate is 50 to 200 rpm, and the stirring time is 12 to 16 hours.
[0017] As a preferred embodiment of the preparation method of the present invention, the scraping film is placed in deionized water, wherein the scraper used for scraping the film has a thickness of 150 μm and the temperature of the deionized water is 25°C.
[0018] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a biomass blended membrane material, characterized in that the biomass blended membrane material can be applied to the field of sewage treatment.
[0019] As a preferred embodiment of the application of the present invention, the biomass blended membrane material is used to remove Fe3+ The adsorption efficiency of pollutants can reach over 99.9%.
[0020] Beneficial effects of the present invention:
[0021] (1) The present invention successfully improves the hydrophilicity and acid resistance of the PVDF ultrafiltration membrane by adding tannic acid, successfully removes metal ions, and has an adsorption efficiency of nearly 100%, with significant anti-pollution effect.
[0022] (2) The blended membrane prepared by the present invention has long-term membrane regeneration ability, and can maintain an adsorption capacity close to or even reaching 100% in five consecutive adsorption tests, and will not be damaged by long-term exposure to a desorption solution with a pH of 1; the blended membrane prepared by the present invention also has a high-efficiency separation ability. After loading metal ions, the permeability of the blended membrane is stably improved, achieving high-efficiency separation of oil and metal mixed solutions and retention of organic pollutants up to 97.84%. It has great application potential in heavy metal adsorption, organic pollutant retention and oil-water separation, and can be effectively used in sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0024] Figure 1 Infrared spectra of PVDF membranes with different TA concentrations.
[0025] Figure 2 SEM images of PVDF membranes with different TA concentrations.
[0026] Figure 3 These are SEM images of PVDF membranes with different TA concentrations after acid immersion.
[0027] Figure 4 This is a graph showing the retention performance test results of PVDF membranes with different TA concentrations after acid immersion.
[0028] Figure 5 The performance test results of PVDF membranes with different TA concentrations after passing humic acid are shown.
[0029] Figure 6 The graph shows the heavy metal adsorption cycle performance test results of PVDF membranes with different TA concentrations.
[0030] Figure 7The graphs show the heavy metal retention rate of PVDF membranes with different TA concentrations after five adsorption cycles, the changes in BSA retention and permeation flux, and the contact angle test results of TA membranes loaded with different amounts of iron ions.
[0031] Figure 8 The membrane surface of PVDF membrane after adsorption of different concentrations of TA for one hour.
[0032] Fig. 9 This is the result of the separation cycle test of PVDF membrane oil and iron mixed solution with different TA concentrations.
[0033] Fig.10 This is a diagram of the Tyndall effect in the test of the embodiment. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] The raw materials and reagents used in the embodiments of the present invention: polyvinylidene fluoride (PVDF) was purchased from Solvay; N, N-dimethylacetamide (DMAC) was purchased from Shanghai Lingfeng; tannic acid (Tannic Acid) was purchased from Shanghai Lingfeng; anhydrous ferric chloride (Fecl3) was purchased from Shanghai McLean; bovine serum albumin (BSA) Aladdin; hydrochloric acid (HCL) was purchased from Shanghai Lingfeng; soybean oil was purchased from Yihai Kerry Golden Dragon Fish Cereals, Oils and Foods Co., Ltd.
[0038] The instruments used in the embodiments of the present invention are as follows: a vacuum drying oven (QSH-VHX, ALARGE) is used to dry and dehumidify the polymer; an electronic balance (XPE-105, Sartorius) is used to weigh the medicine; a vortex oscillator is used to oscillate the membrane; an ultrapure water machine (E2-30TH, EPED) is used to obtain experimental water; a magnetic stirrer (MR Hei-Tec, HE1DOLPH) is used to stir the casting liquid; an ultraviolet visible spectrophotometer (UV-1900, AOE) is used to test the membrane retention and adsorption effects; a freeze dryer (Refrigerantdryer) is used to store the sample; a scanning electron microscope (SUPRA55, Hitachi) is used to photograph the sample morphology; and a Fourier infrared instrument (Nicolet IS50, Nicolet IS50, USA) is used to measure the chemical groups of the membrane.
[0039] Example 1
[0040] The preparation of PVDF base film comprises the following steps:
[0041] Take out the PVDF powder placed in a drying oven at 70°C, weigh 17.2g of DMAC organic solvent and put it in a glass bottle, weigh 2.8g of PVDF powder and put it in the bottle, and stir it at 70°C on a magnetic heating stirrer for more than 12 hours until the casting solution becomes transparent and viscous;
[0042] Turn off the agitator, remove the casting solution and let it stand to degas;
[0043] Lay the non-woven fabric on a dry and flat glass plate, select a scraper with a thickness of 150 μm, and place the film in 25° C. deionized water after scraping; during this period, change the water two to three times to maintain continuous phase transformation of the membrane system to obtain a PVDF membrane.
[0044] The prepared PVDF membrane was selectively cut and stored for subsequent testing.
[0045] Example 2
[0046] The preparation of PVDF / TA membrane includes the following steps:
[0047] The PVDF powder was taken out from the 70°C drying oven, and 0.1 g, 0.2 g, 0.3 g, and 0.4 g of TA powder were weighed and added to a glass bottle containing 17.2 g of DMAC organic solvent, and finally 2.8 g of PVDF powder was added. After the glass bottle was sealed, it was placed on a 70°C heating stirrer and stirred for more than 12 hours to prepare a casting solution;
[0048] The non-woven fabric was laid on a dry and flat glass plate, and the scraper thickness was selected to be 150 μm. After scraping the film, it was placed in 25° C. deionized water to obtain PVDF / TA mixed matrix membranes with different concentrations.
[0049] Example 3
[0050] This example is to characterize and analyze the films obtained in Example 1 and Example 2:
[0051] (1) FTIR analysis: The test was conducted by attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR, Nicolet IS50). Before the test, the frozen and cut membranes were freeze-dried. The analysis results are shown in Figure 2. Figure 1 As shown, 1041cm -1 and 1096cm -1 The absorption band at 1724 cm is the CH stretching vibration of the aromatic ring of tannic acid. -1 The peak at 1069 cm is caused by C=O stretching vibration. -1 The peak corresponds to C-OH stretching vibration, 1609 cm -1 The peaks belong to aromatic CO stretching vibrations. These results indicate that tannic acid is successfully blended into the PVDF membrane system.
[0052] (2) SEM analysis: The test was conducted using a field emission scanning electron microscope (SEM, SUPRA55). The cut membranes were freeze-dried before testing and then sent for testing. The morphology of the surface, cross-section, and internal finger-like pore layer of the membranes with different tannic acid contents was studied by SEM observation. The results are as follows: Figure 2 As shown, Figure 2 (a) and (f) are SEM images of pure PVDF membrane. Figure 2 (b) and (g) are SEM images of 0.5wt% TA films. Figure 2 (c) and (h) are SEM images of 1wt% TA films. Figure 2 (d) and (i) are SEM images of 1.5wt% TA film. Figure 2 (e) and (j) are SEM images of 2 wt % TA films.
[0053] From the surface morphology, it can be seen that with the increase of tannic acid addition content, the surface porosity shows a trend of gradual increase, mainly due to the hydrophilicity of tannic acid, which leads to an increase in the phase change rate. From the cross-section, it can be seen that the PVDF membrane and the blended membrane have a typical ultrafiltration membrane asymmetric structure with a skin layer, finger-like pores and sponge pores in the bottom layer. With the increase of tannic acid addition content, finger-like pores appear and the area they occupy gradually becomes larger. These results are mainly due to the fact that the large amount of phenolic hydroxyl groups rich in tannic acid itself can attract water molecules through hydrogen bonding, and obtain a faster phase transformation speed than pure PVDF membrane during the phase transformation process, resulting in larger finger-like pores.
[0054] (3) Pure water flux test: The pure water permeability (PWP) of the membrane was tested at a transmembrane pressure (TMP) of 1 bar using a cross-flow device. Before the test, the membrane was pre-pressed with pure water at 2 bar for 20 minutes to ensure the stability of the membrane. PWP was calculated using the following formula:
[0055] PWP=Q / (ΔP×A×t)
[0056] Where Q is the permeate volume of water (L), ΔP is the TMP (bar), and A is the effective area (m 2 ), t is the filtration time (min), where A is 9.616 cm 2 .
[0057] Table 1
[0058] Basement membrane 0.5wt%TA 1.0wt%TA 1.5wt%TA 2.0wt%TA Film thickness / micron 20~25 20~25 20~25 20~25 20~25 Finger hole length / micrometer 6~8 10 12 13 17 <![CDATA[Water flux (Lm -2 h -1 )]]> 47 93 94 156 169
[0059] The characterization analysis results are shown in Table 1. It can be seen that the addition of tannic acid improves the structure of the membrane, increases the length of the finger-like pores, and reduces the mass transfer resistance. Therefore, the water flux increases from 47 L m -2 h -1 Increased to 169L m -2 h -1 .
[0060] Example 4
[0061] This example is to conduct an acid resistance test on the films prepared in Example 1 and Example 2.
[0062] The prepared PVDF membranes with different TA concentrations were immersed in a hydrochloric acid solution with a pH of 1 and exposed for 50 hours. During this period, the membranes were taken out every 10 hours and rinsed with deionized water, and then soaked for more than one hour to remove the residual acid. Finally, 0.1 g / LBSA was used as the pollutant feed to test the retention performance.
[0063] The acid-soaked membrane was subjected to SEM analysis using a field emission scanning electron microscope (SEM, SUPRA55). The analysis results are shown in Figure 3 As shown, Figure 3 (a) is the SEM image of pure PVDF membrane. Figure 3 (b) and (c) are acid leaching SEM images of pure PVDF membrane; Figure 3 (d) is the SEM image of 0.5wt% TA. Figure 3 (e) and (f) are acid leaching SEM images of 0.5wt% TA; Figure 3(g) is the SEM image of 2wt% TA. Figure 3 (h) and (i) are acid leaching SEM images of 2 wt% TA.
[0064] The morphology of the surface, cross section and internal finger-like pore layer of the blended membrane and the base membrane after exposure to acid for 50 hours was studied by SEM observation. Except for 0.5wt%, the base membrane and the membrane with 2wt% addition content all collapsed to varying degrees. Compared with base membrane a and b, the membrane pores expanded on the surface and the structure was damaged on the cross section. The 2wt% TA had pore collapse. This is because tannic acid itself has a certain acidity as tannic acid. Excessive addition will affect the stability of the membrane. In addition, the viscosity of the 2wt% blended casting liquid system is higher than that of the membrane with other addition contents during phase inversion, which will lead to agglomeration and then the result of different tannic acid contents in some parts after film formation. The parts with more tannic acid contents obtain more protons during the protonation process, which eventually leads to membrane damage. In summary, in the process of heavy metal adsorption, the tannic acid blended membrane has a certain acid stability ability. Therefore, TA / PVDF ultrafiltration membrane can use HCL with pH=1 as the membrane cleaning solvent.
[0065] Retention performance test: The retention of bovine serum albumin (BSA) by the membrane was tested at a transmembrane pressure (TMP) of 1 bar using a cross-flow system. The concentration of BSA was measured at 280 nm using an ultraviolet spectrophotometer. R was calculated using the following formula:
[0066]
[0067] Where R is the interception rate (%), C p is the permeate concentration (g·L -1 ), C f is the stock solution concentration (g·L -1 ).
[0068] The interception performance test results are as follows Figure 4As shown, in the experiment, it was observed that the retention capacity of the base membrane decreased by 50% after immersion for 10 hours, while the blended membrane still maintained about 85% of the retention capacity after 50 hours of exposure. In particular, the retention capacity of the 2wt% blended membrane decreased by 30% after 50 hours, which is consistent with the characterization results of the SEM image. In other words, tannic acid concentrations less than or equal to 1.5wt% have better acid resistance. If the tannic acid concentration is 2.0wt%, when the acid immersion time is greater than 20 hours, there is a trend of decreased retention performance, showing a decrease in acid resistance. This is because the excessive concentration of tannic acid increases the porosity of the membrane structure and reduces the acid resistance stability. It should be noted that the retention capacity of the base membrane increased after 20 hours of exposure, which is attributed to the damage of the membrane structure. The pressure in the cross-flow device causes excessive squeezing of the fragile parts of the structure, blocking the pores, resulting in the inability of BSA pollutants to pass through in large quantities.
[0069] Example 5
[0070] This example is to test the performance of the membranes prepared in Example 1 and Example 2.
[0071] The pure water permeability (PWP) of the prepared PVDF membranes with different TA concentrations was tested at a transmembrane pressure (TMP) of 1 bar for 1 h using a cross-flow filtration device. -1 The humic acid solution was used to test the flux and retention performance of the PVDF / TA modified membrane for humic acid, and then the membrane that was tested with humic acid was rinsed and soaked in deionized water for 10 hours to test its anti-pollution performance, and pure water was passed through it to test its pure water flux at 0.1Mpa.
[0072] The interception performance calculation formula is the same as that in Example 4, and the pure water flux calculation formula is the same as that in Example 3.
[0073] Anti-pollution performance test: The membrane that was tested with humic acid was rinsed and soaked with deionized water for 10 hours, then immersed in deionized water for storage. Before the test, it was rinsed with deionized water for 5 minutes. The FRR was calculated as follows:
[0074]
[0075] Where FRR (Flux recovery rate) is the membrane flux recovery rate (%), Jw is the original membrane pure water flux (L·m -2 ·h -1 ), Jr is the pure water flux after immersion or hydrochloric acid shock (L·m -2 ·h -1 );
[0076] Rr is calculated by the following formula:
[0077]
[0078] Where Rr (Reversible ratio) is the reversible contamination rate (%), JL is the flux when filtering humic acid, BSA or adsorbing ferric chloride solution (L·m -2 ·h -1 );
[0079] Rir is calculated by the following formula:
[0080]
[0081] Where Rir (Irreversible ratio) is the irreversible contamination rate (%);
[0082] Rt is calculated by the following formula:
[0083]
[0084] Where Rt is the total contamination rate (%).
[0085] The test results of membrane performance after humic acid was introduced are as follows: Figure 5 As shown, Figure 5 (a) is the pure water flux test result, Figure 5 (b) is the interception performance test result, Figure 5 (c) is the anti-pollution performance test result.
[0086] It can be seen that the retention rate increases with the increase of tannic acid content and decreases with the increase of membrane flux. This is because the molecular weight of humic acid is too small and can be carried through the membrane pores by water molecules with a fast flow rate. At the same time, in the flux recovery test, the recovery effect of the blended membrane is slightly lower than that of the base membrane. This is caused by the humic acid molecules staying in the membrane pores, while most of the base membrane stays on the surface. Despite this, the retention rate of the blended membrane is still above 92%.
[0087] Example 6
[0088] This example is to conduct an adsorption cycle test on the membranes prepared in Example 1 and Example 2.
[0089] The prepared PVDF membranes with different TA concentrations were tested for pure water permeability (PWP) of TA-modified membranes at 1 bar transmembrane pressure (TMP) using a cross-flow device for 1 h, and then 0.1 g·L -1 The adsorption flux and interception performance of the PVDF / TA modified membrane for metallic iron ions were tested by ferric chloride solution. The membrane was then shaken with hydrochloric acid at pH = 1 for 5 minutes to remove surface contamination. The membrane was then rinsed with deionized water for five minutes to test anti-pollution performance, contact angle, and pure water flux at 0.1 MPa. This cycle was repeated five times, and finally 0.1 g·L-1 The BSA solution was used to test the flux and retention performance of BSA of the PVDF / TA modified membrane after 5 cycles. Then the membrane was soaked for 10 hours and then passed pure water to test its pure water flux at 0.1 MPa.
[0090] Retention and adsorption performance test: The concentrations of BSA and ferric chloride solution were measured at 280 nm and 290 nm using an ultraviolet spectrophotometer, and the calculation formula was the same as that in Example 4.
[0091] Contact angle test: Tested by water contact angle meter (JC2000D1), the freeze-dried membrane was cut into small pieces, double-sided tape was pasted on the glass, and the cut small pieces of membrane were pasted flat on the double-sided tape. During the test, water drops were dropped on the surface of the membrane, and the water drop size was set to 0.5μL by computer. Each membrane was tested at least 6 times.
[0092] The pure water flux calculation formula is the same as that in Example 3, and the anti-pollution performance test calculation formula is the same as that in Example 5.
[0093] The heavy metal adsorption cycle test results of PVDF membranes with different concentrations of TA are shown in Figure 2. Figure 6 , Figure 7 , Figure 8 As shown, Figure 6 The heavy metal adsorption cycle performance test results of PVDF membranes with different concentrations of TA added; Figure 7 (a) Changes in heavy metal rejection and permeation flux of tannic acid membranes with different addition amounts after five adsorption cycles; Figure 7 (b) is a comparison of BSA retention and permeation flux after five cycles and before the cycles; Figure 7 (c) is the contact angle test result of TA membrane loaded with different contents of iron ions; Figure 8 (a) is the membrane surface after the basement membrane is adsorbed for one hour; Figure 8 (b) The membrane surface after 0.5 wt% TA adsorption for one hour; Figure 8 (c) The membrane surface after 2 wt % TA adsorption for one hour.
[0094] Ferric chloride solution was used as a pollutant to evaluate the adsorption performance of tannic acid blend membranes for metallic iron ions. Figure 6 As shown, at the beginning, the ferric chloride solution was used as the feed solution for filtration. When the content of the blend was 0.5wt% and 1wt%, the flux of the membrane increased significantly. For example, when using 0.5wt% blend membrane filtration, the flux increased from 94.15L / m 2 h increased to 111.62L / m 2h. This is because under the same pressure, the adsorption performance of tannic acid on iron ions improves the permeability. Specifically, when the same amount of iron ions are adsorbed onto the membrane in the same time, the membrane with a low tannic acid content obtains a greater flux improvement. This is because the lower the tannic acid content, the lower the viscosity of the casting liquid can be, which in turn disperses the tannic acid better. In addition, when the same amount of iron is adsorbed, the more tannic acid there is, theoretically the faster the negatively charged hydroxyl group will adsorb the positively charged iron ions, making it easier to form an iron hydroxide metal layer on the membrane surface. To verify this, we photographed the membrane surfaces of membranes with different tannic acid contents after the adsorption of heavy metals (see Figure 8 ). It can be clearly seen that the iron hydroxide metal layer on the surface of the blended membrane containing 2wt% in Figure c is thicker and more seriously polluted. These results fully explain the effect of tannic acid on the performance of the membrane and the metal adsorption process.
[0095] In the experiment, a clear increase in flux was observed in the recovery test after the fourth cycle, and in the fifth recovery test, the recovery rate of the membrane with the addition of 1wt% reached 90.625%. This is due to the coordination effect of tannic acid on iron ions, which led to the successful loading of iron ions on the membrane after multiple cycles. Figure 7 By contrast with (c), it can be found that after tannic acid is loaded with different contents of iron ions, the contact angle decreases significantly, among which 0.5wt% decreases most significantly, with the maximum decrease of 20.14%.
[0096] This experiment combined with actual application, the acid washing time of 5 minutes was used in the cycle test, but this is far from the life limit of the membrane. Therefore, TA can provide sufficient service life in the actual application of biomass blending modified membrane, and has obvious advantages in commercial competition. In addition, due to the metal coordination effect, tannic acid and iron ions are tightly combined, which makes it difficult to fall off, and it is a rare hydrophilic protective layer in the direction of anti-pollution modification. In addition, with the booming battery industry today, the treatment of battery waste liquid is particularly important. Combining the excellent performance of PVDF / TA membrane with a simple production method provides an economical, green and feasible solution.
[0097] Example 7
[0098] This example is to conduct a separation cycle test of the oil and iron mixed solution on the membranes prepared in Examples 1 and 2.
[0099] (1) Preparation of oil-in-water emulsion and 0.1 g·L -1 Ferric chloride mixed solution: 0.1 g / L soybean oil was vigorously stirred at 1500 rpm for 12 h using a stirrer to form an oil-in-water emulsion. 0.1 g ferric chloride was dissolved in the oil-in-water emulsion and stirred again for 3 hours to finally form a mixed solution of oil and ferric chloride.
[0100] (2) The prepared PVDF membranes with different TA concentrations were tested for pure water permeability (PWP) of TA-modified membranes at 1 bar transmembrane pressure (TMP) for 1 h using a cross-flow device. -1 The oil-in-water emulsion prepared by vigorous stirring for 10 h was mixed with 0.1 g·L -1 The ferric chloride mixture was used to test the adsorption flux and retention performance of the PVDF / TA modified membrane for metallic iron ions. The membrane was then shaken with hydrochloric acid at pH 1 for 5 minutes to remove surface contamination. The membrane was then rinsed with deionized water for five minutes to test its anti-pollution performance and pure water was passed through to test its pure water flux at 1 bar. This cycle was repeated three times.
[0101] Interception and adsorption performance test: The concentration of the ferric chloride solution was measured at 290 nm using an ultraviolet spectrophotometer, and the calculation formula was the same as that in Example 4.
[0102] The pure water flux calculation formula is the same as that in Example 3, and the anti-pollution performance test calculation formula is the same as that in Example 5.
[0103] The results of the separation cycle test of oil and iron mixed solution by PVDF membrane with different concentrations of TA are shown in the figure. Fig. 9 , Fig.10 As shown, Fig. 9 (a) The base film and the blended film are subjected to three cycles of the oil and metal mixed solution; Fig. 9 (b) The interception and flux of oil in the mixed solution by the base membrane and the blend membrane; Fig. 9 (c) The interception and flux of iron in the mixed solution by the base membrane and the blended membrane; Fig.10 (a) Tyndall effect of oil-in-water emulsion; Fig.10 (b) Tyndall effect of a mixed solution of oil and iron; Fig.10 (c) Tyndall effect of liquid retention by the blend membrane.
[0104] By comparing the base membrane with the blended membrane, the pollution of the base membrane is more serious than that of the blended membrane. When the base membrane intercepts pollutants for the first time, the oil and metal retention rates are both around 80%, and at the beginning of the second interception, the retention rate increases significantly, which is a significant feature of membrane pore blockage. In comparison, the retention rate of pollutants by the blended membrane remains above 90%. In addition, the first flux recovery of the blended membrane is basically the same as the initial flux, which is due to the adsorption of iron ions to form a protective layer, and the iron ions drive the oil to fall off during pickling and analysis. The experimental results prove the application value of tannic acid blended membranes in electroplating wastewater.
[0105] Comparative Example 1
[0106] According to the document CN113663660A, a heavy metal element adsorption membrane was prepared, PAN was used as the base membrane material, DMAC was used as the solvent, the PAN base membrane was synthesized based on the phase inversion method, and the ZnAl-EDTA modified material was prepared, and Zn(NO 3 ) 2 、Al(NO 3 ) 3 , EDTA and NaOH are mixed as stock solutions, ground and sealed for dry storage to prepare ZnAl-EDTA modified materials, then the ZnAl-EDTA modified materials are weighed separately and fulvic acid is added, mixed and stirred to prepare a gel solution, and the prepared PAN-based membrane is placed in a glass sandwich, and the obtained gel solution is injected into the glass sandwich to obtain a heavy metal adsorption film on the surface of the PAN-based membrane, and the obtained membrane is subjected to interception and adsorption performance tests, and it is found that the best effect is achieved when the temperature is 60°C, the maximum adsorption amount is only 68 mg / g, and the temperature conditions are demanding.
[0107] Comparative Example 2
[0108] According to Example 3 of document CN107198974A, a photocatalytic hollow fiber ultrafiltration membrane was prepared. The retention and adsorption performance of the prepared membrane was tested, and it was found that the removal rate of the membrane for metal ions did not exceed 30%.
[0109] The present invention successfully improves the hydrophilicity and acid resistance of the PVDF ultrafiltration membrane by adding tannic acid to the membrane, and successfully removes metal ions through the principle of coordination between phenolic hydroxyl groups and iron ions, with an adsorption efficiency close to 100%. The hydrophilicity of the hydroxyl group is utilized to significantly improve the anti-pollution effect.
[0110] The blended membrane prepared by the present invention has long-term membrane regeneration ability, and can maintain an adsorption capacity close to or even reaching 100% in five consecutive adsorption tests, and will not be damaged by long-term exposure to a desorption solution with a pH of 1; the blended membrane prepared by the present invention also has a high-efficiency separation ability, and the permeability of the blended membrane is stably improved after loading metal ions, achieving high-efficiency separation of oil and metal mixed solutions and retention of organic pollutants up to 97.84%, and has great application potential in heavy metal adsorption, organic pollutant retention and oil-water separation, and can be effectively applied to sewage treatment.
[0111] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. An application of a biomass blended membrane material, characterized in that: The biomass blended membrane material is used to remove Fe from water 3+ The adsorption efficiency of pollutants is over 99.9%; The casting solution of the biomass blended membrane material is composed of tannic acid TA, polyvinylidene fluoride PVDF and N, N-dimethylacetamide DMAC; wherein the weight of TA accounts for 0.5-1.5% of the total weight of PVDF and DMAC; The biomass blended membrane material has a typical ultrafiltration membrane asymmetric structure of a skin layer, finger-shaped pores and a bottom layer of sponge pores. In the membrane thickness of 150 μm, the finger-shaped pores of the blended membrane occupy about 70% of the membrane thickness, and its water flux is 100 L m -2 h -1 ~200 L m -2 h -1 ; The biomass blended membrane material has hydrophilicity, acid resistance, long-term membrane regeneration ability and high-efficiency separation ability; The preparation method of the biomass blended membrane material comprises: The TA powder, PVDF powder and DMAC organic solvent are mixed, heated and stirred to prepare a film casting solution; The casting solution is spread on a dry carrier covered with non-woven fabric, the film is scraped, and the film is placed in deionized water to obtain a PVDF / TA mixed matrix membrane, which is a biomass blend membrane; The mass ratio of the TA powder, PVDF powder and DMAC organic solvent is 0.1~0.3:2.8:17.2; The heating and stirring, wherein the heating temperature is 50-80°C, the stirring rate is 50-200 rpm, and the stirring time is 12-16h.
2. The use of the biomass blended membrane material as claimed in claim 1, characterized in that: The scraping film is placed in deionized water, wherein the scraper used for scraping the film has a thickness of 150 μm and the temperature of the deionized water is 25°C.
Citation Information
Patent Citations
Photocatalytic hollow fiber ultrafiltration film and preparation method thereof
CN107198974A
Preparation method of heavy metal element adsorption film
CN113663660A
CND-PVDF (Carboxylated Nanodiamond-Polyvinylidene Fluoride) hydrophilic anti-pollution ultra-filtration membrane, and preparation method and application thereof
CN109569324A